Descritores das ligações químicas S-H e C-S em derivados de tiofenol - Barbosa, Willis Galvíncio (2024)
This study delves into the chemical nuances of thiophenols and their derivatives through a comprehensive computational analysis, employing different methods from the traditional energetic perspectives such as bond dissociation enthalpy and S−H dissociation dynamics. By employing the overlap model along with its topological descriptors (OP/TOP), quantum theory of atoms in molecules (QTAIM), and local vibrational mode (LVM) theories, the research provides an alternative perspective of the S−H and C−S bonding scenarios in substituted thiophenols. The investigation follows the electron-donating capacity of S−H substituent variation with the nature and positioning of other ring substituents. Energy profile analyses indicate distinct stability differences in the cis and trans conformations of meta- and para-PhSH systems, influenced by the electron-donating strength of these substituents. The study also uncovers significant variations in S−H bond distances and descriptor values, particularly in para-substituted PhSH, reflecting the influence of electron-donating or withdrawing substituents. In contrast, alterations at the meta-position show minimal effects on C−S bond descriptors, while para-substitutions markedly influence C−S bond characteristics, demonstrating a clear correlation with the electron-donating or withdrawing capabilities of the substituents. This research sheds light on the intricate bond dynamics in aromatic systems with diverse substituents, highlighting the complex interaction between electronic effects and molecular conformation. The study employs the ωB97X-D/Def2TZVP level of theory for molecular geometries, ensuring accurate characterization of structures as true minima via analytical harmonic frequency determination. The electronic properties of S−H and C−S bonds in variously substituted thiophenols were analyzed using OP/TOP, QTAIM, and LVM methodologies. Computational processes, including conformational scans, geometry optimizations, and vibrational frequency calculations, were conducted using Gaussian 09, with ultra-fine integration grids and tight convergence criteria for the SCF procedure. Bond descriptors were computed utilizing ChemBOS, Multiwfn, and LModeA software, providing a robust and detailed examination of bond properties.